Narrative Of The Feminine Inthe Better Man - Hema R, M.Poonkodi (International Journal of Advanced Science and Technology, 2020)
Anita Nair’s novels are a combination of liberal voices of Indian women and the domineering voices of myths in day- to- day life. The present paper analyses the role of narrative techniques of memory, flashback and stream of consciousness in The Better Man. The paper further analyses the functions of narrative in drawing contrasts and parallels between women of the past and present. The women characters subsequently evolve and mould themselves into individuals with free thought and identity. Nair’s novels overthrow her repeated assertion that she is not a feminist. Her women characters prove themselves to be strong and assertive. The narrative techniques throws light on their struggles to free themselves from the mythological, social and familial shackles.